Mechanism of hepatoprotective action of bile salts in liver disease - Stiehl, Adolf; Petersen-Benz, Christine; Sauer, Peter (Gastroenterology clinics of North America, 1999)
Ursodeoxycholic acid (UDCA) improves liver enzymes and in many instances liver histology in cholestatic liver diseases, such as primary biliary cirrhosis (PBC) and primary sclerosing cholangitis (PSC). In PBC, UDCA improves survival free of liver transplantation; and in PSC, UDCA improves survival only if dominant strictures of the bile ducts are recognized early and treated endoscopically. UDCA seems to have a beneficial effect in cholestasis of pregnancy, cholestasis of cystic fibrosis, various other cholestatic diseases of childhood as well as cholestasis of total parenteral nutrition. Besides classic cholestatic diseases, UDCA also improves liver biochemistry in alcoholic liver disease and in chronic viral hepatitis C. In chronic hepatitis, UDCA has no effect on liver histology, and its role is unclear; moreover, it is unclear whether UDCA has an effect when combined with interferon treatment. Of considerable interest is the observation that survival of patients undergoing liver transplantation may be improved by treatment with UDCA. The main target of UDCA treatment is cholestasis, and consequently the mechanisms responsible for the beneficial effects in these diseases are of interest.